La traduzione dell’anamnesi dall’italiano al polacco: studio comparativo di documenti medici - Maniowska, Katarzyna (Neophilologica, 2019)
According to the principles of medical art, anamnesis is an examination that enables to formulate hypothesis regarding patient’s illness, its origin and eventually prognosis. The difficulties related to translation of such documents are due to the fact that it is a very inhomogeneous type of text made of quotations of patient’s words, their reinterpretations and more detailed objective information added by the doctor. In the very moment of translation into another language, the translator of such documents should be able to distinguish at the lexical, morphological and syntactical level these two different ways of narration. Consequently, the translator of this kind of texts is obliged to distinguish terminological choices in order to translate the text appropriately. Serious linguistic and medical consequences may arise during translation of medical anamnesis if subjective and objective perceptions are mixed in one text. The aim of the present paper based on comparative studies of Italian medical documents translated into Polish is to find possible syntactical and morphological solutions that have arisen in the translation process.